V. I. Lenin y las fuerzas armadas soviéticas / [N. Pankratov...(et al.) ; presentación de Víctor Kuziakov ; traducido del ruso por Joaquín Rodríguez - Pankratov, N. R. (Nikolai Rodionovich)
Bibliografía